Determinants Of Financial Literacy, Digital Literacy, Internet Penetration And Consumer Confidence Level Mediated By Fintech Growth On Retail Industry Growth In Indonesia - Sapta Rini, Anggarwati; Mukti Soma, Abdul (International Journal of Educational Research & Social Sciences, 2024)
This study evaluates how financial literacy, digital literacy, internet penetration, and consumer confidence influence retail industry growth in Indonesia, emphasizing the mediating role of fintech. In the era of industry 4.0, technology, especially fintech, has transformed conventional financial business models into digital ones, accelerating transactions and financial inclusion. The Covid-19 pandemic has further driven digitalization, although it has posed major challenges for the retail industry. This study aims to determine the actual impact of the development of fintech applications including the influence of financial literacy, digital literacy, internet penetration and consumer confidence levels on the development or growth of retail in Indonesia. This study uses a quantitative method with a focus on analyzing the relationship between financial literacy, digital literacy, internet penetration, and consumer confidence levels in the growth of the retail industry, both directly and through the mediation of fintech growth. The data used are secondary data that include information on the financial literacy index, digital literacy index, internet penetration level, consumer confidence index, fintech adoption level, and retail performance indicators. To overcome incomplete data, imputation and proxy variable methods are used. The analysis was conducted using multiple linear regression to identify direct relationships between variables, and structural equation modeling (SEM) to comprehensively evaluate the influence of fintech mediation. This study shows that financial literacy, digital literacy, and consumer confidence levels have a significant influence on retail growth, both with and without fintech growth mediation. Digital literacy and consumer confidence levels have a positive impact, reflecting that understanding of digital technology and consumer confidence contribute to retail development. Conversely, financial literacy shows a negative influence. Internet penetration does not show a significant influence on retail growth, either directly or through fintech mediation.